Influence of HIV-1 infection on the presence of HPV in uterine cervix lesions - Fernandes, Ana Paula M.; Gonçalves, Maria Alice G.; Simões, Renata T.; Quintana, Silvana Maria; Duarte, Geraldo; Donadi, Eduardo A. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction:the infection with oncogenic human papillomavirus (HPV), including HPV16 and HPV18, is considered to be the major risk factor forcervical cancer development. Among HIV-positive women, studies have reported an increased prevalence and persistence of HPV16 and HPV18explaining, in part, the increased susceptibility for squamous intraepithelial lesion (SIL) development, which is a precursor lesion of the cervical can-cer. Objective:to analyse the influence of HIV-1 infection towards HPV 16 and HPV18 infection presence in women presenting SIL. Methods:cer-vical biopsies from 42 women presenting with SIL, with or without HIV-1 infection were studied for the presence and HPV typing, using the polime-rase chain reaction. Statistical analysis was performed using Fisher`s exact test. Results:all patients (100%) presented with active HPV infection.HPV16 was the type more frequently detected, followed by HPV18 and other HPV types. Patients presenting with HIV-1 infection together withdecreased CD4+ cell counts showed increased oncogenic HPV infection (p = 0.04), and HPV16 was the predominant type (p = 0.01).Conclusion:thepresence of active oncogenic HPV infection may be an important factor contributing to SIL installation; primarily among immunocompromissedHIV-1 positive women exhibiting lower CD4+ cell counts.